ANALISIS PENGGUNAAN MODEL ALTMAN (Z-SCORE) UNTUK MEMPREDIKSI POTENSI KEBANGKRUTAN - Wulandari, Maya; Bakara, Sarah; Hasibuan, Alawi Parlindungan; Ruslan, Dede (Jurnal Bina Bangsa Ekonomika, 2025)
The bankruptcy of a company can be evaluated and measured through the analysis of financial statements. By conducting this analysis, the company's management can understand the financial condition and developments, as well as the results that have been achieved in the past and present. Knowing the health level of a company is essential to improve operational efficiency, so that the ability to generate profits can be improved and the risk of bankruptcy can be minimized. In addition, financial health analysis also allows companies to assess their ability to meet short-term obligations, the effectiveness of asset use, and the results of sales. In this article, the Altman Model (Z-Score) is used, by applying the Altman model, companies can make a more in-depth assessment of their financial situation